Electrostatic spinning chitosan-polycaprolactone-nanocellulose nanofiber membrane as well as preparation method and application thereof
Through electrospinning technology, chitosan, polycaprolactone and nanocellulose are combined, and curcumin and carvacrol are added as antibacterial components, which solves the problems of poor mechanical strength, poor antibacterial effect and poor stability of existing antibacterial food packaging materials, achieving efficient and stable antibacterial effect and good mechanical properties.
Patent Information
- Application Number
- CN202410904066.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-08
- Publication Date
- 2025-04-25
AI Technical Summary
The existing degradable antibacterial food packaging materials have problems such as poor mechanical strength, poor antibacterial effect and unstable antibacterial properties.
Electrospinning technology was used to combine chitosan, polycaprolactone and nanocellulose, and curcumin and carvacrol were added as antibacterial components, and nanofiber membranes were prepared by regulating component ratios and treatment conditions.
It significantly improves the antibacterial effect and stability of the nanofiber membrane, while enhancing its mechanical properties, making it suitable for high-quality antibacterial packaging materials.
Smart Images

Figure BDA0004931445200000171 
Figure BDA0004931445200000181 
Figure BDA0004931445200000191
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of food antibacterial preservation, and in particular to an electrostatically spun chitosan-polycaprolactone-nanocellulose nanofiber membrane and a preparation method and application thereof. Background Art
[0002] With the development of social economy and the accelerated pace of life, people's demand for safety, nutrition and health is constantly increasing, which has promoted the continuous development of high-tech in the food industry. However, food hygiene and safety issues are still hot issues in today's society and have received widespread attention from the public. Simply achieving the degradability of packaging materials cannot fully meet the needs of food packaging. Microbial contamination in food is one of the main factors leading to food corruption and deterioration, and it is also a problem that food packaging materials need to focus on. The electrospinning method uses electrostatic force to decompose polymer solutions into continuous micron or nanostructured fibers. These fibers have the advantages of high specific surface area, high porosity, and multifunctionality. Therefore, the use of electrospinning technology to develop environmentally friendly, biodegradable and antibacterial food packaging has a positive leading role in developing new functional packaging materials and ensuring food safety.
[0003] Chitosan is highly favored for its good biocompatibility and outstanding antibacterial properties. Polycaprolactone, as a synthetic polyester, has become a hot raw material in the field of food packaging due to its excellent mechanical properties and processing flexibility. However, the membrane material obtained by electrospinning chitosan and polycaprolactone has the problem of low mechanical strength. At present, in order to improve the mechanical strength of the membrane material, a reinforcing phase is usually added to the obtained membrane material, but there is a problem that the reinforcing phase has poor compatibility with the composite phase of chitosan and polycaprolactone, which affects the physical and chemical properties of the final material.
[0004] Curcumin has been widely studied in the food industry for its antioxidant and antibacterial properties. Carvacrol has excellent broad-spectrum antibacterial properties. This non-specific antibacterial effect has enabled carvacrol to be fully developed in the field of antibacterial. At present, the research on antibacterial films with curcumin and carvacrol as antibacterial active ingredients mainly focuses on combining curcumin or carvacrol with a matrix alone, and the antibacterial broad-spectrum, antibacterial effect and stability of existing antibacterial films have not reached a high level.
[0005] Therefore, there is an urgent need in the art to develop a nanofiber membrane with excellent antibacterial effect, strong stability, and good mechanical properties that can be used as a high-quality antibacterial packaging material. Summary of the invention
[0006] The purpose of the present invention is to provide an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane and a preparation method and application thereof, so as to solve the problems of poor mechanical strength, poor antibacterial effect and unstable antibacterial performance of existing degradable antibacterial food packaging materials.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The present invention provides a method for preparing an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane, comprising the following steps:
[0009] (1) Preparation of nano antibacterial particle solution: curcumin, carvacrol, zein solution and water are mixed and then subjected to rotary evaporation to obtain a zein nano particle solution; the zein nano particle solution, sodium alginate and water are mixed and then centrifuged to obtain a supernatant which is the nano antibacterial particle solution;
[0010] (2) Preparation of nanofiber membrane: chitosan, polycaprolactone, nanocellulose and solvent are mixed to obtain a spinning solution; nano antibacterial particle solution is added to the spinning solution and mixed to obtain a mixed solution; the mixed solution is subjected to electrostatic spinning to obtain a nanofiber membrane.
[0011] Preferably, the zein solution is a mixture of zein and ethanol solution; the dosage ratio of zein to ethanol solution is 8-12 mg: 1-1.5 mL; and the mass fraction of ethanol solution is 70-90%.
[0012] Preferably, the dosage ratio of curcumin, carvacrol, zein and water is 1.5-2 mg: 1 mg: 40-50 mg: 20-30 mL; the mixing time of the curcumin, carvacrol, zein solution and water is 20-40 min; the temperature of the rotary evaporation is 30-50° C., and the rotary evaporation time is 20-40 min.
[0013] Preferably, after the rotary evaporation, water is used to replenish the volume of the product obtained by rotary evaporation to the volume before rotary evaporation.
[0014] Preferably, the dosage ratio of the zein nanoparticle solution, sodium alginate and water is 1-3 mL: 3-5 mg: 2-3 mL; the centrifugal speed is 3000-4000 r / min, and the centrifugal time is 5-20 min.
[0015] Preferably, the solvent comprises acetic acid; the dosage ratio of the chitosan, polycaprolactone, nanocellulose and solvent is 0.5-0.8g:7-9g:0.5-0.9g:50-80mL; the dosage of the nano antibacterial particle solution is 0.5-2.5% of the mass of the spinning solution.
[0016] Preferably, in the step (2), the mixing time is 5 to 10 minutes, and after mixing, the spinning solution is ultrasonically treated, the power of the ultrasonic treatment is 500 to 800 W, and the time of the ultrasonic treatment is 8 to 12 minutes.
[0017] Preferably, the electrospinning parameters are as follows: positive voltage is 20 to 23 kV, negative voltage is -2.9 to -2.5 kV, propulsion speed is 0.2 to 0.4 mm / min, and the distance between the syringe needle and the receiver is 8 to 12 cm.
[0018] The present invention also provides the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane prepared by the preparation method of the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane.
[0019] The present invention also provides application of the electrospun chitosan-polycaprolactone-nanocellulose nanofiber film in biodegradable antibacterial food packaging.
[0020] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention combines curcumin and carvacrol as antibacterial components, and the antibacterial effect of the obtained nanofiber membrane can be significantly improved by adjusting the dosage ratio of curcumin and carvacrol; in addition, the antibacterial component-loaded zein-sodium alginate nanoparticles are obtained by reacting the antibacterial component, zein and sodium alginate, which can significantly improve the stability of the antibacterial component;
[0022] (2) The present invention significantly improves the tensile strength and elongation at break of the obtained nanofiber membrane by combining chitosan, polycaprolactone and nanocellulose as the matrix of the nanofiber membrane. The combination of chitosan and polycaprolactone makes the nanofiber membrane have excellent mechanical properties, biocompatibility, processing flexibility and antibacterial properties, and further improves the compatibility between the various components of the matrix and the compatibility between the matrix and the nano-antibacterial particles. There is a significant physical bond between chitosan and nanocellulose. Nanocellulose as a reinforcing phase can significantly improve the mechanical strength of the obtained nanofiber membrane, and nanocellulose is a biodegradable substance that will not have an impact on the environment. DETAILED DESCRIPTION
[0023] The present invention provides a method for preparing an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane, comprising the following steps:
[0024] (1) Preparation of nano antibacterial particle solution: curcumin, carvacrol, zein solution and water are mixed and then subjected to rotary evaporation to obtain a zein nano particle solution; the zein nano particle solution, sodium alginate and water are mixed and then centrifuged to obtain a supernatant which is the nano antibacterial particle solution;
[0025] (2) Preparation of nanofiber membrane: chitosan, polycaprolactone, nanocellulose and solvent are mixed to obtain a spinning solution; nano antibacterial particle solution is added to the spinning solution and mixed to obtain a mixed solution; the mixed solution is subjected to electrostatic spinning to obtain a nanofiber membrane.
[0026] In step (1) of the present invention, the specific steps of mixing curcumin, carvacrol, zein solution and water are: firstly dissolving curcumin and carvacrol in zein solution to obtain a mixed solution containing curcumin and carvacrol, and then dripping the mixed solution containing curcumin and carvacrol into water; the dripping rate is preferably 0.5 to 2 mL / s, and more preferably 1 to 1.5 mL / s.
[0027] In the present invention, the zein solution is a mixture of zein and ethanol solution; the dosage ratio of zein to ethanol is preferably 8-12 mg: 1-1.5 mL, more preferably 9-11 mg: 1.1-1.4 mL, and more preferably 10 mg: 1.2-1.3 mL; the ethanol solution is an ethanol-water solution; the mass fraction of ethanol is preferably 70-90%, more preferably 75-85%, and more preferably 80%.
[0028] In the present invention, the dosage ratio of curcumin, carvacrol, zein and water is preferably 1.5-2 mg: 1 mg: 40-50 mg: 20-30 mL, more preferably 1.6-1.9 mg: 1 mg: 42-48 mg: 23-27 mL, more preferably 1.7-1.8 mg: 1 mg: 45-46 mg: 25-26 mL; the mixing time of the curcumin, carvacrol, zein solution and water is preferably 20-40 min, more preferably 25-35 min, more preferably 30 min; the rotary evaporation temperature is preferably 30-50° C., more preferably 35-45° C., more preferably 40-42° C.; the rotary evaporation time is preferably 20-40 min, more preferably 25-35 min, more preferably 30 min.
[0029] In the present invention, water is used after the rotary evaporation to supplement the volume of the product obtained by the rotary evaporation to the volume before the rotary evaporation.
[0030] In step (1) of the present invention, the specific steps of mixing the zein nanoparticle solution, sodium alginate and water are: first dissolving sodium alginate in water, adjusting the pH value, and then adding the zein nanoparticle solution thereto; the pH value after adjusting the pH value is preferably 4.0-4.5, more preferably 4.1-4.4, and more preferably 4.2-4.3.
[0031] In the present invention, the dosage ratio of the corn protein nanoparticle solution, sodium alginate and water is preferably 1-3 mL: 3-5 mg: 2-3 mL, more preferably 1.5-2.5 mL: 3.5-4.5 mg: 2.2-2.5 mL, more preferably 2-2.2 mL: 3.8-4 mg: 2.3-2.4 mL; the centrifugal speed is preferably 3000-4000 r / min, more preferably 3200-3500 r / min, more preferably 3300-3400 r / min; the centrifugal time is preferably 5-20 min, more preferably 10-18 min, more preferably 12-15 min.
[0032] In the present invention, the nanocellulose includes cellulose nanofibrils; the nanocellulose is obtained by mechanical shearing of wood cellulose; the diameter of the nanocellulose is preferably 10 to 50 nm, more preferably 20 to 40 nm, and more preferably 30 to 35 nm; the length of the nanocellulose is preferably 1 to 5 μm, more preferably 2 to 4 μm, and more preferably 3 μm.
[0033] In the present invention, the solvent includes acetic acid; the dosage ratio of the chitosan, polycaprolactone, nanocellulose and solvent is preferably 0.5-0.8g:7-9g:0.5-0.9g:50-80mL, further preferably 0.6-0.7g:7.5-8.5g:0.6-0.8g:60-70mL, more preferably 0.65g:7.6-8g:0.65-0.7g:65mL; the dosage of the nano antibacterial particle solution is preferably 0.5-2.5% of the mass of the spinning solution, further preferably 1-2% of the mass of the spinning solution, and more preferably 1.5-1.8% of the mass of the spinning solution.
[0034] In step (2) of the present invention, the mixing time is preferably 5 to 10 min, more preferably 6 to 9 min, and more preferably 7 to 8 min; after mixing, ultrasonic treatment is performed to obtain the spinning solution, and the power of the ultrasonic treatment is preferably 500 to 800 W, more preferably 600 to 700 W, and more preferably 650 W; the time of ultrasonic treatment is preferably 8 to 12 min, more preferably 9 to 11 min, and more preferably 10 min.
[0035] In the present invention, the parameters of the electrospinning are as follows: the positive voltage is preferably 20 to 23 kV, more preferably 20.71 to 22.25 kV; the negative voltage is preferably -2.9 to -2.5 kV, more preferably -2.92 to -2.65 kV; the propulsion speed is preferably 0.2 to 0.4 mm / min, more preferably 0.3 mm / min; the distance between the syringe needle and the receiver is preferably 8 to 12 cm, more preferably 9 to 11 cm, and more preferably 10 cm.
[0036] The present invention also provides the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane prepared by the preparation method of the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane.
[0037] The present invention also provides application of the electrospun chitosan-polycaprolactone-nanocellulose nanofiber film in biodegradable antibacterial food packaging.
[0038] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0039] The preparation steps of the nanocellulose used in the following examples and comparative examples are as follows: sugarcane bagasse is mechanically sheared to obtain nanocellulose with a diameter of 30 nm and a length of 3 μm.
[0040] Example 1
[0041] This embodiment provides a method for preparing an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane, comprising the following steps:
[0042] (1) Preparation of zein nanoparticle solution: 500 mg of zein was dissolved in 50 mL of 80% ethanol aqueous solution, and mixed to obtain a zein solution; 20 mg of curcumin and 10 mg of carvacrol were dissolved in the zein solution, and mixed for 30 min to obtain a mixed solution; the mixed solution was added dropwise to ultrapure water at a rate of 0.5 mL / s, and after the addition was completed, the obtained product was placed in a rotary evaporator and rotary evaporated at 40° C. for 30 min. After the rotary evaporation was completed, ultrapure water was added to the same volume as after the addition was completed, and the zein nanoparticle solution was obtained;
[0043] (2) Preparation of nano antibacterial particle solution: 40 mg of sodium alginate was dissolved in 30 mL of ultrapure water and the pH value was adjusted to 4 to obtain a sodium alginate solution; 3 mL of zein nanoparticle solution was placed in the sodium alginate solution, mixed well, and centrifuged at 3000 r / min for 15 min. The supernatant was the nano antibacterial particle solution.
[0044] (3) Preparation of nanofiber membrane: 0.6 g chitosan, 8 g polycaprolactone, 0.5 g nanocellulose and 70 mL 92% acetic acid aqueous solution were mixed to obtain a spinning solution; the nano-antibacterial particle solution was added to the spinning solution, mixed for 8 min, and ultrasonically treated at a power of 600 W for 10 min. The amount of the nano-antibacterial particle solution was 1% of the mass of the spinning solution to obtain a mixed solution; the mixed solution was subjected to electrospinning to obtain a nanofiber membrane; the electrospinning parameters were: a 5 mL disposable syringe with a 20G metal needle (inner diameter of 0.60 mm), a positive voltage of 22.15 kV, a negative voltage of -2.88 kV, a propulsion speed of 0.3 mm / min, a distance between the syringe needle and the receiver of 10 cm, and the nanofiber membrane was collected on the roller of the receiver.
[0045] The embedding rate of the nano antibacterial particles prepared in this embodiment is 92.3%, the average particle size is 238.59nm, the morphology is complete, the surface is smooth, and the structure is compact. The retention rate of the nano antibacterial particles after 3 hours of ultraviolet irradiation can reach 42.05%. The retention rate of the nano antibacterial particles after soaking in a 35% hydrochloric acid aqueous solution for 30 minutes can reach 84.51%, and the retention rate of the nano antibacterial particles after soaking in a 50% sodium chloride aqueous solution for 30 minutes can reach 88.51%, which has good stability.
[0046] In the electrospinning process of this embodiment, a large amount of filaments can be produced, a stable Taylor cone can be formed, and stable, smooth and bead-free fibers can be formed.
[0047] Example 2
[0048] This embodiment provides a method for preparing an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane, comprising the following steps:
[0049] (1) Preparation of zein nanoparticle solution: 500 mg of zein was dissolved in 50 mL of 85% ethanol aqueous solution, and mixed to obtain a zein solution; 18 mg of curcumin and 10 mg of carvacrol were dissolved in the zein solution, and mixed for 30 min to obtain a mixed solution; the mixed solution was added dropwise to ultrapure water at a rate of 1 mL / s, and after the addition was completed, the obtained product was placed in a rotary evaporator and rotary evaporated at 40° C. for 30 min. After the rotary evaporation was completed, ultrapure water was added to the same volume as after the addition was completed, and the zein nanoparticle solution was obtained;
[0050] (2) Preparation of nano antibacterial particle solution: 35 mg of sodium alginate was dissolved in 30 mL of ultrapure water and the pH value was adjusted to 4 to obtain a sodium alginate solution; 2.5 mL of zein nanoparticle solution was placed in the sodium alginate solution, mixed, and centrifuged at 3000 r / min for 20 min. The supernatant was the nano antibacterial particle solution;
[0051] (3) Preparation of nanofiber membrane: 0.65 g chitosan, 8 g polycaprolactone, 0.6 g nanocellulose and 70 mL 92% acetic acid aqueous solution were mixed to obtain a spinning solution; the nano-antibacterial particle solution was added to the spinning solution, mixed for 8 min, and ultrasonically treated at a power of 600 W for 10 min. The amount of nano-antibacterial particle solution was 1.5% of the mass of the spinning solution to obtain a mixed solution; the mixed solution was subjected to electrospinning to obtain a nanofiber membrane; the electrospinning parameters were: a 5 mL disposable syringe with a 20G metal needle (inner diameter of 0.60 mm), a positive voltage of 20.03 kV, a negative voltage of -2.5 kV, a propulsion speed of 0.3 mm / min, a distance between the syringe needle and the receiver of 10 cm, and the nanofiber membrane was collected on the roller of the receiver.
[0052] The embedding rate of the nano antibacterial particles prepared in this embodiment is 91.8%, the average particle size is 240.1nm, the morphology is complete, the surface is smooth, and the structure is compact. The retention rate of the nano antibacterial particles after 3 hours of ultraviolet irradiation can reach 47.15%. The retention rate of the nano antibacterial particles after soaking in a 35% hydrochloric acid aqueous solution for 30 minutes can reach 85.42%, and the retention rate of the nano antibacterial particles after soaking in a 50% sodium chloride aqueous solution for 30 minutes can reach 87.86%, which has good stability.
[0053] In the electrospinning process of this embodiment, a large amount of filaments can be produced, a stable Taylor cone can be formed, and stable, smooth and bead-free fibers can be formed.
[0054] Example 3
[0055] This embodiment provides a method for preparing an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane, comprising the following steps:
[0056] (1) Preparation of zein nanoparticle solution: 500 mg of zein was dissolved in 50 mL of 80% ethanol aqueous solution, and mixed to obtain a zein solution; 20 mg of curcumin and 10 mg of carvacrol were dissolved in the zein solution, and mixed for 30 min to obtain a mixed solution; the mixed solution was added dropwise to ultrapure water at a rate of 1 mL / s, and after the addition was completed, the obtained product was placed in a rotary evaporator and rotary evaporated at 40° C. for 30 min. After the rotary evaporation was completed, ultrapure water was added to the same volume as after the addition was completed, and the zein nanoparticle solution was obtained;
[0057] (2) Preparation of nano antibacterial particle solution: 50 mg of sodium alginate was dissolved in 30 mL of ultrapure water and the pH value was adjusted to 4.2 to obtain a sodium alginate solution; 3 mL of zein nanoparticle solution was placed in the sodium alginate solution, mixed, and centrifuged at 3000 r / min for 20 min. The supernatant was the nano antibacterial particle solution;
[0058] (3) Preparation of nanofiber membrane: 0.7 g chitosan, 8.5 g polycaprolactone, 0.7 g nanocellulose and 80 mL 90% acetic acid aqueous solution were mixed to obtain a spinning solution; the nano-antibacterial particle solution was added to the spinning solution, mixed for 8 min, and ultrasonically treated at a power of 600 W for 10 min. The amount of the nano-antibacterial particle solution was 2% of the mass of the spinning solution to obtain a mixed solution; the mixed solution was subjected to electrospinning to obtain a nanofiber membrane; the electrospinning parameters were: a 5 mL disposable syringe with a 20G metal needle (inner diameter of 0.60 mm), a positive voltage of 21.53 kV, a negative voltage of -2.58 kV, a propulsion speed of 0.3 mm / min, a distance between the syringe needle and the receiver of 10 cm, and the nanofiber membrane was collected on the roller of the receiver.
[0059] The embedding rate of the nano antibacterial particles prepared in this embodiment is 89.1%, the average particle size is 239.54nm, the morphology is complete, the surface is smooth, and the structure is compact. The retention rate of the nano antibacterial particles after 3 hours of ultraviolet irradiation can reach 48.84%. The retention rate of the nano antibacterial particles after soaking in a 35% hydrochloric acid aqueous solution for 30 minutes can reach 86.02%, and the retention rate of the nano antibacterial particles after soaking in a 50% sodium chloride aqueous solution for 30 minutes can reach 87.98%, which has good stability.
[0060] In the electrospinning process of this embodiment, a large amount of filaments can be produced, a stable Taylor cone can be formed, and stable, smooth and bead-free fibers can be formed.
[0061] Comparative Example 1
[0062] This comparative example provides a method for preparing an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane. The difference between the preparation steps and those of Example 1 is that the amount of carvacrol is adjusted to 20 mg, and the rest is the same as in Example 1.
[0063] The embedding rate of the nano antibacterial particles prepared in this comparative example is 65.23%, the average particle size is 258.45nm, and most of the particles are incomplete in shape and have protrusions on the surface. The retention rate of the nano antibacterial particles after 3 hours of ultraviolet irradiation can reach 23.52%. The retention rate of the nano antibacterial particles after soaking in a 35% hydrochloric acid aqueous solution for 30 minutes can reach 72.31%, and the retention rate of the nano antibacterial particles after soaking in a 50% sodium chloride aqueous solution for 30 minutes can reach 75.14%.
[0064] In the electrospinning process of this comparative example, a large amount of filaments can be produced, a stable Taylor cone can be formed, and stable, smooth and bead-free fibers can be formed.
[0065] Comparative Example 2
[0066] This comparative example provides a method for preparing an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane. The difference between the preparation steps and those of Example 1 is that the addition of carvacrol is omitted, and the rest is the same as Example 1.
[0067] The embedding rate of the nano antibacterial particles prepared in this comparative example is 72.31%, the average particle size is 232.43nm, the morphology is complete, the surface is smooth, and the structural density is unevenly distributed. The retention rate of the nano antibacterial particles after 3 hours of ultraviolet irradiation can reach 45.21%. The retention rate of the nano antibacterial particles after soaking in a 35% hydrochloric acid aqueous solution for 30 minutes can reach 83.02%, and the retention rate of the nano antibacterial particles after soaking in a 50% sodium chloride aqueous solution for 30 minutes can reach 85.13%.
[0068] In the electrospinning process of this comparative example, a large amount of filaments can be produced, a stable Taylor cone can be formed, and stable, smooth and bead-free fibers can be formed.
[0069] Comparative Example 3
[0070] This comparative example provides a method for preparing an electrospun chitosan-polycaprolactone nanofiber membrane. The difference between the preparation steps and those of Example 1 is that the addition of nanocellulose is omitted, and the rest is the same as Example 1.
[0071] In the electrospinning process of this comparative example, the filaments are unstable, and the needle tip has filaments accumulated over time. The surface of the formed nanofiber membrane is rough, and the fibers have a bead-like structure.
[0072] Comparative Example 4
[0073] This comparative example provides a method for preparing an electrospun polycaprolactone-nanocellulose nanofiber membrane. The difference between the preparation steps and those of Example 1 is that the addition of chitosan is omitted, and the rest is the same as Example 1.
[0074] In the electrospinning process of this comparative example, the filaments are unstable, and the needle tip has filaments accumulated over time. The surface of the formed nanofiber membrane is rough, and the fibers have a bead-like structure.
[0075] Comparative Example 5
[0076] This comparative example provides a method for preparing an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane. The difference between the preparation steps and those of Example 1 is that the amount of chitosan is adjusted to 1 g, and the rest is the same as Example 1.
[0077] The electrospinning process in this comparative example was stable, and the formed fibers had a bead-like structure.
[0078] Comparative Example 6
[0079] This comparative example provides a method for preparing an electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane. The difference between the preparation steps and those of Example 1 is that the amount of polycaprolactone is adjusted to 11 g, and the rest is the same as Example 1.
[0080] The electrospinning process in this comparative example was stable, and the formed fibers had a bead-like structure.
[0081] Characterization and performance testing:
[0082] 1. Determination of viscosity and conductivity of electrospinning mixed solution and diameter of nanofiber membrane:
[0083] 1.1 Method for measuring viscosity and conductivity of electrospinning mixed solution: The viscosity and conductivity of the electrospinning mixed solution of Examples 1 to 3 and Comparative Examples 1 to 6 were measured using a viscometer and a conductivity meter, respectively.
[0084] 1.2 Method for determining the diameter of nanofiber membrane: Use ImageJ image processing software to measure the diameter of the nanofiber, select electron microscope pictures, randomly select 50 fibers for each sample, calculate the single fiber diameter and get the average value, the samples are the nanofiber membranes obtained in Examples 1 to 3 and Comparative Examples 1 to 6.
[0085] 1.3 Determination results:
[0086] The viscosity and conductivity of the mixed solution of electrospinning in Examples 1 to 3 and Comparative Examples 1 to 6 and the diameter of the nanofiber membrane are measured as shown in Table 1.
[0087] Table 1 Viscosity and conductivity of the mixed solution of electrospinning of Examples 1 to 3 and Comparative Examples 1 to 6 and the measurement results of the diameter of the nanofiber membrane
[0088] Sample Viscosity (mPa·s) Conductivity (μS / cm) Diameter(nm) Example 1 896 92.3 180.65 Example 2 914 95.4 192.54 Example 3 902 93.4 189.41 Comparative Example 1 889 91.1 176.54 Comparative Example 2 892 92.0 178.68 Comparative Example 3 826 85.2 170.54 Comparative Example 4 774 80.5 165.43 Comparative Example 5 932 97.5 198.02 Comparative Example 6 941 98.0 198.34
[0089] As shown in Table 1, due to the presence of non-covalent interactions such as hydrogen bonds between chitosan and polycaprolactone molecules, and the presence of physical bonding between chitosan and nanocellulose, as the concentration of chitosan, nanocellulose and polycaprolactone increases, the interaction between molecules is enhanced, resulting in an increase in the overall viscosity of the electrospinning mixed solution. The conductivity of the electrospinning mixed solution is mainly affected by the type and concentration of the solvent and biopolymer used. When the concentrations of chitosan, nanocellulose and polycaprolactone increase, the conductivity of the electrospinning mixed solution has a significant increasing trend. The conductivity of the electrospinning mixed solution directly affects the extension level of the jet under the action of the high-voltage electric field. Increasing the conductivity of the electrospinning mixed solution can enhance the stability of the spinneret jet, thereby helping to form uniform fibers.
[0090] 2 Determination of mechanical strength of nanofiber membrane:
[0091] 2.1 Determination method: Cut the sample into a rectangular strip of 5 cm × 1 cm in size, randomly select five points on each sample, and use a handheld outside micrometer to measure and calculate the average thickness. Then use a tensile testing machine to measure the sample, use formula (1) to determine the elongation at break, and use formula (2) to determine the tensile strength; set the initial clamping distance of the tensile testing machine to 25 mm, and the tensile speed to 5 mm / min; the sample is the nanofiber membrane obtained in Examples 1 to 3 and Comparative Examples 1 to 6.
[0092]
[0093] In formulas (1) and (2), F max is the maximum load (N); W is the width (mm); d is the thickness (mm); L is the length at break (mm); L0 is the initial clamping distance (mm).
[0094] 2.2 Measurement results: The measurement results of the tensile strength and elongation at break of the nanofiber membranes of Examples 1 to 3 and Comparative Examples 1 to 6 are shown in Table 2.
[0095] Table 2 Determination results of tensile strength and elongation at break of nanofiber membranes of Examples 1 to 3 and Comparative Examples 1 to 6
[0096]
[0097] As shown in Table 2, due to the non-covalent interactions such as hydrogen bonds between chitosan and polycaprolactone molecules, and the physical bonding between chitosan and nanocellulose, as the concentrations of chitosan, nanocellulose and polycaprolactone increase, the intermolecular interactions are enhanced, which can improve the tensile strength and elongation at break of the nanofiber membrane to a certain extent. However, as the concentrations of chitosan and polycaprolactone further increase, the tensile strength and elongation at break of the nanofiber membrane will gradually decrease. This is because the aggregation of chitosan and polycaprolactone itself may weaken the intermolecular interaction between chitosan and polycaprolactone, resulting in a gradual decrease in tensile strength and elongation at break.
[0098] 3. Determination of Antioxidant Activity of Nanofiber Membranes:
[0099] 3.1 Determination method: The antioxidant activity of the nanofiber membrane is determined by the scavenging ability of DPPH free radicals. At room temperature, 40 mg of each of the nanofiber membranes of Examples 1 to 3 and Comparative Examples 1 to 6 were weighed and mixed with 8 mL of 0.1 mol / L DPPH ethanol solution, and a blank control group was set up and placed in a dark environment for reaction for 2 hours. The absorbance of each solution was measured at 517 nm. The determination was calculated using formula (3):
[0100]
[0101] In formula (3), A0 is the absorbance (Abs) of the blank control group; A1 is the absorbance (Abs) of the reaction group.
[0102] 3.2 Test results: The test results of the antioxidant activity of the nanofiber membranes of Examples 1 to 3 and Comparative Examples 1 to 6 are shown in Table 3.
[0103] Table 3 Antioxidant activity test results of nanofiber membranes of Examples 1 to 3 and Comparative Examples 1 to 6
[0104]
[0105]
[0106] As shown in Table 3, chitosan itself has a certain antioxidant capacity. After adding different amounts of nano-antibacterial particles, the free radical scavenging ability of the nanofiber membrane gradually increased. This is related to the antioxidant capacity of curcumin and carvacrol in the nano-antibacterial particles. And with the increase of carvacrol concentration, the antioxidant capacity of the prepared nanofiber membrane weakened, indicating that the dosage ratio of carvacrol to curcumin has an effect on the antioxidant capacity of the nanofiber membrane. The improvement of the antioxidant performance of the nanofiber membrane helps to prevent the oxidation of food lipids, and may also reduce or avoid the addition of synthetic antioxidants in food, thereby improving food safety.
[0107] 4. Antibacterial performance test of nanofiber membrane:
[0108] 4.1 Detection method: Staphylococcus aureus and Escherichia coli preserved in -20℃ glycerol were cultured in a 37℃ constant temperature incubator with an inoculum size of 4% for 12 hours. After two activations, the bacterial solution was centrifuged at 3000r / min for 5 minutes, the supernatant was discarded, and the bacterial concentration was adjusted to about 10 with sterile water. 8 CFU / mL. Take a 12-well plate, place the above-mentioned nanofiber membrane of the same size and a commercially available PE film disc as a control in each well, and add 1mL of the above-mentioned bacterial suspension. Then put it in a photodynamic blue light device for illumination for 1 hour. After the irradiation is completed, add sterile water and shake for 5 minutes, take 100μL and spread it on LB solid culture medium, and determine the total number of colonies according to the standard to examine the inhibitory effect of the fiber membrane on the two bacteria, and record the dilution multiple at the same time. The unit of the number of colonies in each group is in the form of logarithm Log (CFU / mL).
[0109] The fiber membranes are the nanofiber membranes of Examples 1 to 3 and Comparative Examples 1 to 6, and their antibacterial properties are tested respectively using the above method.
[0110] 4.2 Test results: The test results of the antibacterial properties of the nanofiber membranes of Examples 1 to 3 and Comparative Examples 1 to 6 are shown in Table 4.
[0111] Table 4 Antibacterial performance test results of nanofiber membranes of Examples 1 to 3 and Comparative Examples 1 to 6
[0112]
[0113] As shown in Table 4, the nanofiber membrane has a significant antibacterial effect on Staphylococcus aureus and Escherichia coli. This is because curcumin in the nano-antibacterial particles produces active oxygen under blue light excitation, combined with the broad-spectrum antibacterial effect of carvacrol, which destroys bacterial cells. Since Gram-negative bacteria have a more complex cell wall structure than Gram-positive bacteria, the antibacterial nanofiber membrane has a significantly better inhibitory effect on Staphylococcus aureus than Escherichia coli under photodynamic action. It can be seen that the nanofiber membrane can effectively inhibit the growth of microorganisms on the surface of food, thereby delaying the deterioration and corruption of food, and helping to extend the shelf life of food.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a nanofiber membrane of electrospun chitosan-polycaprolactone-nanocellulose, characterized in that: The steps include: (1) Preparation of nano antibacterial particle solution: curcumin, carvacrol, zein solution and water are mixed and then subjected to rotary evaporation to obtain a zein nano particle solution; the zein nano particle solution, sodium alginate and water are mixed and then centrifuged to obtain a supernatant which is the nano antibacterial particle solution; (2) Preparation of nanofiber membrane: chitosan, polycaprolactone, nanocellulose and solvent are mixed to obtain a spinning solution; nano antibacterial particle solution is added to the spinning solution and mixed to obtain a mixed solution; the mixed solution is subjected to electrostatic spinning to obtain a nanofiber membrane.
2. The method for preparing the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane according to claim 1, characterized in that: The zein solution is a mixture of zein and ethanol solution; the usage ratio of zein to ethanol solution is 8-12 mg: 1-1.5 mL; and the mass fraction of ethanol solution is 70-90%.
3. The method for preparing the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane according to claim 2, characterized in that: The dosage ratio of the curcumin, carvacrol, zein and water is 1.5-2 mg: 1 mg: 40-50 mg: 20-30 mL; the mixing time of the curcumin, carvacrol, zein solution and water is 20-40 min; the temperature of the rotary evaporation is 30-50° C., and the rotary evaporation time is 20-40 min.
4. The method for preparing the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane according to any one of claims 1 to 3, characterized in that: After the rotary evaporation, water is used to supplement the volume of the product obtained by rotary evaporation to the volume before rotary evaporation.
5. The method for preparing the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane according to claim 4, characterized in that: The dosage ratio of the corn protein nanoparticle solution, sodium alginate and water is 1-3 mL: 3-5 mg: 2-3 mL; the centrifugal speed is 3000-4000 r / min, and the centrifugal time is 5-20 min.
6. The method for preparing the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane according to claim 5, characterized in that: The solvent comprises acetic acid; the dosage ratio of the chitosan, polycaprolactone, nanocellulose and solvent is 0.5-0.8g:7-9g:0.5-0.9g:50-80mL; the dosage of the nano antibacterial particle solution is 0.5-2.5% of the mass of the spinning solution.
7. The method for preparing the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane according to claim 5 or 6, characterized in that: In the step (2), the mixing time is 5 to 10 minutes, and after mixing, the spinning solution is subjected to ultrasonic treatment, the power of the ultrasonic treatment is 500 to 800 W, and the time of the ultrasonic treatment is 8 to 12 minutes.
8. The method for preparing the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane according to claim 7, characterized in that: The parameters of the electrospinning are as follows: positive voltage is 20-23 kV, negative voltage is -2.9-2.5 kV, propulsion speed is 0.2-0.4 mm / min, and the distance between the syringe needle and the receiver is 8-12 cm.
9. The electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane prepared by the method for preparing the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane according to any one of claims 1 to 8.
10. Use of the electrospun chitosan-polycaprolactone-nanocellulose nanofiber membrane according to claim 9 in biodegradable antibacterial food packaging.
Citation Information
Patent Citations
Preparation method of nano cellulose / chitosan / polycaprolactone porous scaffold
CN105169477A
Carvacrol-loaded zein-based nanoparticles and preparation method thereof
CN115844007A
Preparation method of zein-sodium alginate composite membrane for embedding curcumin
CN116554519A
Antibacterial preservative film containing composite nanoparticles and preparation method thereof
CN116675884A
Cited By
Coaxial electrospinning radiation phase change cooling fiber membrane and preparation method thereof
CN121519263A